Optimalisasi Peran Petani Millenial Dalam Usahatani Sayuran sebagai Pendukung Rumah Pangan Lestari di Desa Kelising Kabupaten Bulungan - Zulhafandi; Aulia, Wella; Agang, MW; Santoso, Dwi; Mubarak, Ahmad; Hendris, Hendris; Arbain, Muhammad; Banyuriatiga, Banyuriatiga; Khaerunnisa, Khaerunnisa; sari, Nove Kurnianti; Tanjung, Hery Bachrizal (Progran Studi Farmasi Universitas Mandala Waluya, 2024)
Millennial farmers are a young generation who have great potential in bringing positive changes in the agricultural sector. To maintain food security and the environment, it takes an active role of farmers, especially millennial farmers, in developing vegetable farming as a supporter of sustainable food houses. With the number of productive age population, it allows them to be actively involved in maintaining family food security by utilizing yard land to be planted with vegetables and various medicinal plants. Service activities were carried out in Kelising Village, Sekatak District, Bulungan Regency, North Kalimantan. The mechanism of activities is divided into several stages, namely survey, socialization, training and evaluation of activities. Training activities are the main activities in this service by providing training through skills in cultivating land/planting media, vegetable cultivation, vegetable care and marketing. This service activity was followed by quite high enthusiasm from the people of Kelising Village because previously they did not want to be involved in agriculture due to wrong perceptions about agriculture. With the assistance, training and motivation provided, it is hoped that the interest of the community, especially the young ones, to become millennial farmers will increase and it is hoped that Kelising Village can become a leader in the use of yard land through its millennial farmers.